Penaksiran Kadar Al2O3 Pada Endapan Bauksit Laterit Dengan Metode Ordinary Kriging (OK) Dan Inverse Distance Weighting (IDW) Untuk Estimasi Jumlah Sumberdaya Bauksit (Al2O3) Di PT Sandai Kemakmuran Utama Kabupaten Ketapang Kalimantan Barat (Jurnal Geomine, 2020)
The application of the interpolation method in assessing levels and thickness provides a significant benefit to resource estimation. The technique used in this study is the Ordinary Kriging (OK) and the Inverse Distance Weighting (IDW) methods. The estimation of each method gives the value of RMSE (Root Mean Square Error) from the results of cross-validation. RMSE value as parameter used in assessing the performance of each method. The model with the smallest RMSE amount chosen as the best. The study conducted rendering data from the 104 pit exploration test results. In the OK interpolation method, experimental variogram fitting performed by using the spherical, exponential, and gaussian models. In this study, the smallest RMSE value for overburden thickness estimation obtained best variogram model is exponential. While, for ore thickness estimation, the best variogram is spherical, for estimating Al2O3 levels, the best variogram is exponential. Estimated measured resources from the expected OK results obtained total OB volume is 791,927.6768 BCM and 1,341,549.615 tons of ore with an average content of 41.881% Al2O3. According to the evaluation, power parameters in the IDW method found that the smallest RMSE value in the estimated thickness of OB uses IDW power 2, in ore thickness estimation uses IDW power 5, in the opinion of Al2O3 levels using IDW power 4. Estimated measured resources from IDW results obtained total volume OB is 770,009.6711 BCM and 1,329,135.518 tons of ore with an average content of 42.075% Al2O3. From the analysis with best interpolation method, the best way for estimating OB thickness is the IDW (power 2), for ore thickness estimation is the OK (spherical), for determining Al2O3 level is IDW (power 4) method, the estimated resource results the total OB volume is 770,009.6711 BCM and 1,323,541.218 tons of ore with an average content of 42.065% Al2O3.